Transit ridership survey by analysis validation of electronic pass tickets - A. I. Fadeev; S. Alhusseini (Вестник СибАДИ, 2021)
Introduction. The methods used today for determining the demand on public transport come with a big waste of time, resources and a need for great effort. In this regard, a special perspective is to study the transit demand based on the collection, integration and analysis of large and diverse data, which were generated by various sources of human life: Urban computing, Big data, Internet of things.Materials and methods. This article presents a method for determining (restoring) the correspondence of transit passengers by means of intelligent analysis of validation operations data of electronic travel tickets (smart card, transport card, magnetic card, mobile phone or other electronic devices (electronic gadgets)), which are recorded in the automated transportation management system during validation.Results. The algorithm for calculating passenger correspondence is implemented in a computer program using the relational DBMS MS SQL Server. The effectiveness of the proposed algorithm was verified by calculating the passenger correspondence of public transport in the city of Krasnoyarsk (Russia).Discussion and conclusion. The described method for calculating passenger flows, based on analyzing the data of validation operations of electronic tickets and data from the transit dispatch control system, makes possible to determine the route and passengers correspondence and, to carry out an objective assessment of the demand for public transport and the technical and operational indicators of the transit system.